The Post-Referendum (21F) Situation in Bolivia: Radical Democracy and Institutionalism - Del Aguila, Irma Norka (2024)
This essay undertakes a discursive analysis of three statements made by former vice-president García Linera in the post-referendum juncture. There, it was assumed, under the indigenist populist theory, that the reelection of President Morales was indispensable as he “sutures” the popular field. In the present essay it is stated that the re-election project as a political imperative implied an antagonistic confrontation that could not be solved in the field of the “political”. A radical heterogeneity, with an extreme dislocation of the institutional “floor” was seen as a minor consideration, subordinated to the advance of the “constituent power”. This essay reflects about the role and value of the institutional order in processes where a struggle for radical democracy was at stake.